2008
DOI: 10.1371/journal.pone.0002982
|View full text |Cite
|
Sign up to set email alerts
|

The GCR2 Gene Family Is Not Required for ABA Control of Seed Germination and Early Seedling Development in Arabidopsis

Abstract: BackgroundThe plant hormone abscisic acid (ABA) regulates diverse processes of plant growth and development. It has recently been proposed that GCR2 functions as a G-protein-coupled receptor (GPCR) for ABA. However, the structural relationships and functionality of GCR2 have been challenged by several independent studies. A central question in this controversy is whether gcr2 mutants are insensitive to ABA, because gcr2 mutants were shown to display reduced sensitivity to ABA under one experimental condition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
4

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 26 publications
0
37
0
4
Order By: Relevance
“…An ABA-binding protein endowed with endogenous GTP binding and GTPase activity was also described in Arabidopsis (42). On the one hand, presence of multiple ABA-sensing protein complexes may help explain the fact that loss-of-function mutants of a single receptor may not show a drastic reduction of ABA-sensing capacity (4,5). On the other hand, the ancient evolutionary origin of ABA as a stress signal may justify this apparent redundancy of ABA receptor types.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An ABA-binding protein endowed with endogenous GTP binding and GTPase activity was also described in Arabidopsis (42). On the one hand, presence of multiple ABA-sensing protein complexes may help explain the fact that loss-of-function mutants of a single receptor may not show a drastic reduction of ABA-sensing capacity (4,5). On the other hand, the ancient evolutionary origin of ABA as a stress signal may justify this apparent redundancy of ABA receptor types.…”
Section: Discussionmentioning
confidence: 97%
“…Based on the presence of seven putative transmembrane domains, LANCL1 and -2 were originally described as new G-protein-coupled receptors (GPCR69A and GPR69B, respectively); however, subsequent studies performed on human epithelial cells overexpressing LANCL1 or LANCL2 fused to the green fluorescent protein (LANCL1-GFP and LANCL2-GFP) showed that LANCL1-GFP is mainly found in the cytosol and in the nucleus, whereas LANCL2-GFP is asso-ciated with the plasmamembrane through N-terminal myristoylation (15). Similarly, the debate over the structurally related GCR2 is still open (3)(4)(5)(6)8).…”
mentioning
confidence: 99%
“…58 However, it is important to mention that the characterization of GCR2 as a GPCR and ABA receptor is still a matter of discussion. [59][60][61] More recently, other GPCR-like proteins (GTG1 and GTG2) were identified and its characterization revealed that the GTG proteins represent a novel class of proteins with topology similar to GPCRs but with classic GTP-binding/GTPase activity. 62 Further analysis providing biochemical and phenotypic evidences suggest that GTG1 and GTG2 proteins are redundantly involved in G protein-coupled ABA signaling and are, or are parts of, ABA receptor complexes 62 and their detailed characterization will likely clarify the mechanism underlying the ABA response.…”
Section: Co 2 and Stomatal Developmentmentioning
confidence: 99%
“…Otro supuesto receptor de ABA aislado, GCR2, se propuso también como un receptor acoplado a proteínas G. Actualmente existe cierta controversia acerca tanto sobre su papel en la señalización por ABA [59,70] como en su inclusión en el grupo de receptores acoplados a proteínas G [87,97]. Por un lado esta proteína muestra cierta similitud con una enzima soluble de bacterias de la superfamilia LanC (lantibiotic synthetase component C) [97].…”
Section: Y Enunclassified
“…Se han identificado muchos de los componentes de la ruta de señalización y se ha estudiado la interconexión existente entre ellos para elucidar la estructura de la cascada de señalización del ABA. Estudios de genética molecular, bioquímica y farmacología han llevado a la identificación de más de 100 loci y numerosos mensajeros secundarios que participan en la ruta Otro supuesto receptor de ABA aislado, GCR2, se propuso también como un receptor acoplado a proteínas G. Actualmente existe cierta controversia acerca tanto sobre su papel en la señalización por ABA [59,70] como en su inclusión en el grupo de receptores acoplados a proteínas G [87,97]. Por un lado esta proteína muestra cierta similitud con una enzima soluble de bacterias de la superfamilia LanC (lantibiotic synthetase component C) [97].…”
unclassified